Coccidian infection may explain the differences in the life history of octopus host populations - Storero, Lorena Pia (2013)
The prevalence of coccidian parasites in three Octopus tehuelchus populations from San Matías Gulf (Patagonia, Argentina) is compared. The prevalence was similar between sexes, but varied between seasons (being highest during cold months) and sites. Islote Lobos had the highest prevalence (42.7–100%) followed by San Antonio Bay (0–66%) and El Fuerte (0–24.5%). Octopuses under 27 mm of dorsal mantle length showed a low prevalence (less than 50%), which increased with size. We hypothesize that the high prevalence of parasites, which affect the three populations differentially, could account for the observed variability in life-span and growth, size–frequency distributions, reproduction and densities of O. tehuelchus populations.